RESPONSE OF POMEGRANATE " CV. WONDERFUL" TRANSPLANTS TO MINERAL NUTRITION AND GIBBERRELIC ACID - & Jomaa, Hamdan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate response of pomegranate " Cv. Wonderful" transplants to mineral nutrition and gibberellic acid, it was conducted at the Coll. of Agriculture Engineering Sciences-University of Baghdad, a factorial experiment was according to R.C.B.D. with three replicates for two consecutive growth seasons 2018-2019 to addition six treatments of nue tharyan fertilizer (N.P.K. 20:20:20 and some micronutrients) with three concentrations (0, 2.5, 5 gm.L-1) for each of the soil fertilization and foliar application, and spraying of gibberellic acid (GA3) with three concentrations (0, 50, 100 mg.L-1), and their interaction. Addition of chemical fertilizer to the soil with highest concentration (5 gm.L-1) was the most effective, where led to a significant increases in average of plant height (66.56, 47.05 cm), leaf chlorophyll content (318.3, 323.9 mg.100 g-1 fresh weight) and leaf dry weight (43.51, 50.20 %) for both seasons, respectively. The average of plant height, leaf chlorophyll content and leaf dry weight were increased when sprayed of GA3 at 100 mg.L-1 which reached (71.18, 52.99 cm), (317.5, 322.8 mg.100g-1 fresh weight) and (43.13, 48.15 %) to this traits for both seasons, respectively. the interaction between two factors showed a different effects between highest and lowest on all the traits for both seasons.